Lack of Smoking Knowledge and Behavior among Adolescents during COVID-19 Pandemic in Rural Areas - Purwanta; Yustina Tyas Kurniawati; Rizka Nurul Falaah; Nadia Safa Utami; Qory Nurulita Andayani (Journal of Nursing Management Innovations, 2025)
Background: Indonesia has a high smoking rate and is a leading tobacco producer, with adolescent smoking prevalence increasing from 18.3% to 19.2% in 2019. This study explored smoking knowledge and behavior among 60 male adolescents in rural areas during the COVID-19 pandemic.Methods: This study was conducted in rural areas in Indonesia. We employed a cross-sectional research design and included 60 adolescents, especially males, using data from a questionnaire about smoking knowledge and behavior. The dependent variables included knowledge and behavior of smoking in adolescents that occurred during COVID-19. The independent variables included adolescent-related factors about smoking during COVID-19.Results: Individuals from rural areas in Indonesia started smoking at a very young age and had years of smoking experience using conventional cigarette since then. Receiving counseling about the dangers of smoking was statistically significantly related to good knowledge. Moreover, learning about the susceptibility of smoking to contract (p = 0.007), spread (p = 0.029), worsen symptoms (p < 0.001), and create a higher risk of COVID-19 infection (p = 0.001) can promote good knowledge. More than 50% of adolescents had the intention to decrease smoking around individuals and in the house during COVID-19.Conclusion:Interventions targeting individuals at an early school age are needed. To develop knowledge and behavior about smoking among adolescents in Indonesia, schools should cooperate with other agencies.